Desenvolvimento de imunossensor para detecção de fator de necrose tumoral (TNF-ALFA) - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The development of analytical and low cost methods for fast safe diagnosis and control of illnesses in humans has been one of researchers great interests in the last two decades. This attention is also due to simplicity of use and the great sensitivity in the results. Biosensors based on the surface plasmon resonance (SPR) technique combines the inherent specificity of the recognition elements with high sensitivity of physical transducers, enabling selective and sensitive detection of the analytes of interest without labeling and preliminary purification steps. We proposed the development of a biosensor with immobilized monoclonal antibodies on gold surface, for specific recognition of TNF-α using SPR technique. Design. Anti-TNF-α antibody was covalently immobilized on a gold substrate by silane coupling chemistry. After this, TNF-α antigens aliquots were added on the biosensor surface and the signal was measured during three minutes for TNF-α mass quantification recognized by immobilized antibodies. Results.This biosensor presented 24.0 pg.mm-2 (198,3  28,4) of antibodies immobilized on gold surface. TNF-α human was determined from successive injections, with a linear range from 4.3 up to 34.7 pg/mm-2 (R=0.98, SD=2.18, p<0.0001). Conclusion. We performed a preliminary biosensor to quantify TNF-α for planning of diseases treatment, such as auto immune and periodontal diseases, in which TNF-α inhibitor therapy is usually applied. In this cases, it would be necessary the quantification of this cytokine for therapeutic dose adjustment, improving treatment effectiveness and costs reduction. In the next step we intend to optimize the biosensors conditions preparation as well as to test it in human body fluids samples
Keywords: Biossensor; Imunossensor; Biosensor; Immunosensor; CIÊNCIAS BIOLÓGICAS